2014
DOI: 10.1111/1742-6723.12248
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital management of supraventricular tachycardia in Victoria, Australia: Epidemiology and effectiveness of therapies

Abstract: Patient characteristics associated with SVT are more likely to be middle-aged women with a history of hypertension and hypercholesterolaemia. Therapies were underutilised leading to reduced clinical guideline effectiveness. Where therapies were instigated, reversion rates are greater than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5. In cases where there has been inappropriate administration of adenosine, this had not been associated with adverse outcomes2 6 and, with training, inappropriate administration rates are reduced 7.…”
Section: Introductionmentioning
confidence: 99%
“…Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5. In cases where there has been inappropriate administration of adenosine, this had not been associated with adverse outcomes2 6 and, with training, inappropriate administration rates are reduced 7.…”
Section: Introductionmentioning
confidence: 99%
“…SVT was defined as a regular, narrow complex, tachycardia of ≥140 beats per minute, with a PR interval <0.08 s (or absent or retrograde p‐waves) . A previous study identified that Victorian paramedics were able to correctly interpret SVT on 3‐lead ECG, reporting correct identification of SVT in 119/123 (96.7%, 95% confidence interval [CI] 91.5–99.0) cases …”
Section: Methodsmentioning
confidence: 99%
“…16 A previous study identified that Victorian paramedics were able to correctly interpret SVT on 3-lead ECG, reporting correct identification of SVT in 119/123 (96.7%, 95% confidence interval [CI] 91.5-99.0) cases. 17 The primary study outcome was the proportion of patients in the pre-and post-intervention groups who reverted to sinus rhythm following paramedic management. Secondary outcomes were proportions of reversions following individual therapies (VM, pharmacological agents and Descriptive statistics were used to report demographic and patient-specific factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations